GEREJA SEBAGAI UMAT SISA PADA INTERPRETASI WAHYU 12:17 DAN PENERAPAN MISINYA - Janes Sinaga; Raden Deddy Kurniawan; Juita Lusiana Sinambela (The Way: Jurnal Teologi dan Kependidikan, 2022)
The purpose of this study is that the concept of the remnant for the Adventist Church plays a very important role. Not only in the message of spreading the gospel message to the whole world, but also in understanding who the Adventist Church is. Any religious community that claims to have a special identity and mission can become an arrogant and exclusive community. But that doesn't mean that the claim then automatically makes them like that. The Adventist Church must do what they can to dispel the negative impression of arrogance and exclusivity. Therefore, proper expression is needed to explain the interpretation of the remnant at the end of time to other Christians. Furthermore the Adventist Church can be viewed as a Church relevant to contemporary society. So that the mission of the Adventist Church may be carried out according to divine wisdom. This study uses a qualitative method, by analyzing various sources such as the Bible, library books and several online media and journals. This research is hoped that every Christian understands the meaning of the remnant and knows more about the existence of the Adventist Church. As for the conclusions that can be drawn so that the church becomes exclusive and understands its vocation.